Oocyte–somatic cell interactions in the human ovary—novel role of bone morphogenetic proteins and growth differentiation factors - Chang, Hsun-Ming; Qiao, Jie; Leung, Peter C.K. (Human reproduction update, 2016)
Initially identified for their capability to induce heterotopic bone formation, bone morphogenetic proteins (BMPs) are multifunctional growth factors that belong to the transforming growth factor β superfamily. Using cellular and molecular genetic approaches, recent studies have implicated intra-ovarian BMPs as potent regulators of ovarian follicular function. The bi-directional communication of oocytes and the surrounding somatic cells is mandatory for normal follicle development and oocyte maturation. This review summarizes the current knowledge on the physiological role and molecular determinants of these ovarian regulatory factors within the human germline-somatic regulatory loop. The regulation of ovarian function remains poorly characterized in humans because, while the fundamental process of follicular development and oocyte maturation is highly similar across species, most information on the regulation of ovarian function is obtained from studies using rodent models. Thus, this review focuses on the studies that used human biological materials to gain knowledge about human ovarian biology and disorders and to develop strategies for preventing, diagnosing and treating these abnormalities. Relevant English-language publications describing the roles of BMPs or growth differentiation factors (GDFs) in human ovarian biology and phenotypes were comprehensively searched using PubMed and the Google Scholar database. The publications included those published since the initial identification of BMPs in the mammalian ovary in 1999 through July 2016. Studies using human biological materials have revealed the expression of BMPs, GDFs and their putative receptors as well as their molecular signaling in the fundamental cells (oocyte, cumulus/granulosa cells (GCs) and theca/stroma cells) of the ovarian follicles throughout follicle development. With the availability of recombinant human BMPs/GDFs and the development of immortalized human cell lines, functional studies have demonstrated the physiological role of intra-ovarian BMPs/GDFs in all aspects of ovarian functions, from follicle development to steroidogenesis, cell-cell communication, oocyte maturation, ovulation and luteal function. Furthermore, there is crosstalk between these potent ovarian regulators and the endocrine signaling system. Dysregulation or naturally occurring mutations within the BMP system may lead to several female reproductive diseases. The latest development of recombinant BMPs, synthetic BMP inhibitors, gene therapy and tools for BMP-ligand sequestration has made the BMP pathway a potential therapeutic target in certain human fertility disorders; however, further clinical trials are needed. Recent studies have indicated that GDF8 is an intra-ovarian factor that may play a novel role in regulating ovarian functions in the human ovary. Intra-ovarian BMPs/GDFs are critical regulators of folliculogenesis and human ovarian functions. Any dysregulation or variations in these ligands or their receptors may affect the related intracellular signaling and influence ovarian functions, which accounts for several reproductive pathologies and infertility. Understanding the normal and pathological roles of intra-ovarian BMPs/GDFs, especially as related to GC functions and follicular fluid levels, will inform innovative approaches to fertility regulation and improve the diagnosis and treatment of ovarian disorders.